2015
DOI: 10.1111/acer.12689
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Craving and Ghrelin, Adiponectin, and Resistin Levels in Patients with Alcoholism

Abstract: Although we did not observe a significant relationship between craving and any of the 3 biomarkers on day 0, craving was positively correlated with the levels of adiponectin and ghrelin and negatively correlated resistin levels on day 7. Our findings support the hypothesis that appetite hormones are trait markers for alcohol craving. Nevertheless, more conclusive results require future studies that evaluate the relationship between these hormones and withdrawal/detoxification period or long-term soberness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 43 publications
0
11
0
2
Order By: Relevance
“…The majority of previous clinical studies have found that the plasma concentration of ghrelin is associated with craving in alcohol‐dependent patients. Akkişi Kumsar & Dilbaz () showed a positive correlation between ghrelin concentrations and both, the total score and the score of the compulsive subscale of the Obsessive Compulsive Drinking Scale (OCDS) as well as the score of the resistance subscale of the Penn Alcohol Craving Scale. In addition, our group demonstrated a significant positive correlation between plasma concentrations of acylated ghrelin and alcohol craving as measured with the OCDS at days 1 and 14 of detoxification in 61 alcohol‐dependent male inpatient subjects (Koopmann et al .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of previous clinical studies have found that the plasma concentration of ghrelin is associated with craving in alcohol‐dependent patients. Akkişi Kumsar & Dilbaz () showed a positive correlation between ghrelin concentrations and both, the total score and the score of the compulsive subscale of the Obsessive Compulsive Drinking Scale (OCDS) as well as the score of the resistance subscale of the Penn Alcohol Craving Scale. In addition, our group demonstrated a significant positive correlation between plasma concentrations of acylated ghrelin and alcohol craving as measured with the OCDS at days 1 and 14 of detoxification in 61 alcohol‐dependent male inpatient subjects (Koopmann et al .…”
Section: Discussionmentioning
confidence: 99%
“…Acute alcohol administration results in a reduction in blood ghrelin concentrations or a blunting in fasting-induced ghrelin increase in AUD (Calissendorff et al, 2006, Calissendorff et al, 2005, Zimmermann et al, 2007, Leggio et al, 2013, Ralevski et al, 2017), although these studies have been limited by the use of water or saline as a control condition, rather than an isocaloric non-alcoholic control (see also Commentary by: (Cummings et al, 2007)). Actively drinking AUD individuals seem to have lower circulating ghrelin, but abstinence is associated with increasingly higher circulating ghrelin compared to healthy controls (Kraus et al, 2005, Akkisi Kumsar and Dilbaz, 2015, Wurst et al, 2007, Leggio et al, 2012, Kim et al, 2005, Ralevski et al, 2017). Ghrelin concentrations correlate positively with alcohol craving (Addolorato et al, 2006, Koopmann et al, 2012, Leggio et al, 2012); baseline ghrelin levels are higher in AUD individuals who subsequently relapse, but lower in those able to maintain abstinence (Leggio et al, 2012).…”
Section: Ghrelin Alcohol and Substance Usementioning
confidence: 93%
“…Studies have shown that genetic or metabolic reductions in ghrelin levels decrease alcohol intake ( 100 , 101 ). In addition, higher ghrelin levels are associated with greater self-reported craving ( 97 , 98 , 101 , 102 ), longer and more intense subjective responses to alcohol ( 103 ), and activation of the bilateral insulae ( 104 ) and ventral striatum ( 105 ) as measured with functional magnetic resonance imaging during alcohol cue exposure. Higher levels of ghrelin and activation of the ghrelin receptor stimulate the cholinergic-dopaminergic reward link, which has implications for the reinforcing effects of ghrelin in AUD ( 106 ).…”
Section: Potential Mechanisms Of Action For the Therapeutic Effects Of Ketosis In Alcohol Use Disordermentioning
confidence: 99%